Effect of Carbon Nanofibers on Physical, Adhesion and Rheological Properties of Liquid Epoxidized Natural Rubber Modified Asphalt - Al-Mansob R.A.; Katman H.Y.; Al-Sabaeei A.M.; Zamzami M.; Al-Fakih A.; Wei W.K.; Jassam T.M.; Alsharef J.; Surol S.B.; Yusof N.H.; Koting S. (MDPI, 2023)
Adhesion; Binders; Carbon nanofibers; Elasticity; Hardness; High temperature applications; Rheology; Rubber; Viscoelasticity; Adhesion properties; Carbon nanofibres; Effect of carbons; Elastic balls; Epoxidized natural rubber; Liquid epoxidized natural rubber; Performance; Rheological property; Rheology; Rubber modified asphalt; Liquids